2013
DOI: 10.12693/aphyspola.123.943
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Native Oxide Layers on In+Implanted and Thermally Annealed GaAs

Abstract: Semi-insulating GaAs wafers have been implanted with 250 keV In+ ions at a uence of 3 × 10 16 cm −2 . The samples prepared in this way were subsequently annealed at a temperature of 600• C or 800• C for 2 h. Thicknesses of the native oxide layers on implanted GaAs after samples storage in air were evaluated using the Rutherford backscattering spectrometry with the nuclear reaction O 16 (α, α)O 16 method. The chemical composition of native oxide layers on In + implanted and annealed GaAs has been studied using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…According to the Gibbs phase rule no more than three phases can coexist at equilibrium in a ternary system and therefore it is often useful to represent these phases (neglecting any solid solubility) schematically on the Gibbs triangle [24]. Our recent paper [29] on the chemical composition of native oxide layers covering the implanted and thermally annealed layer on the GaAs surface showed that the formation of Ga 2 O 3 is energetically preferred due to lower Gibbs free energy (− 998.9 kJ/mol) [30]. This is lower than the Gibbs free energies of Ga 2 O, Ga 2 O 3 , As 2 O 3 , As 2 O 5 which are equal to −314.0 kJ/mol, −998.9 kJ/mol, −576.5 kJ/mol and −782.9 kJ/mol, respectively [28].…”
Section: Resultsmentioning
confidence: 99%
“…According to the Gibbs phase rule no more than three phases can coexist at equilibrium in a ternary system and therefore it is often useful to represent these phases (neglecting any solid solubility) schematically on the Gibbs triangle [24]. Our recent paper [29] on the chemical composition of native oxide layers covering the implanted and thermally annealed layer on the GaAs surface showed that the formation of Ga 2 O 3 is energetically preferred due to lower Gibbs free energy (− 998.9 kJ/mol) [30]. This is lower than the Gibbs free energies of Ga 2 O, Ga 2 O 3 , As 2 O 3 , As 2 O 5 which are equal to −314.0 kJ/mol, −998.9 kJ/mol, −576.5 kJ/mol and −782.9 kJ/mol, respectively [28].…”
Section: Resultsmentioning
confidence: 99%